Mixed Methods Study of Physical and Affective Self-Concept among Filipino Adolescents with Polycystic Ovarian Syndrome (PCOS) - Pallasigui, Angelica Irah Mari A.; Dominguez, Jemerson Naceno (Universitas Katolik Soegijapranata, 2024)
Polycystic Ovarian Syndrome (PCOS) is a rare hereditary condition that impact millions of women of reproductive age. Menstrual irregularities, hirsutism, acne, alopecia, obesity, and infertility are all symptoms of PCOS, which is caused by higher-than-normal androgen levels. Furthermore, menstrual irregularity is a prevalent symptom of PCOS and is frequently the first clinical manifestation in adolescents. This study identified the constructs of physical and affective self-concept to increasingly impact adolescents with PCOS as the negative implications of these clinical manifestations affect their perception and belief toward themselves which changes their self-concept or views about their physical self. Also, it impacts their affective self-concept that influences their feeling toward themselves. In this study, the Mindfulness Based Stress Reduction Program (MBSR) was facilitated online to increase the levels of Physical and Affective Self- Concept among sixteen adolescents who were diagnosed with polycystic ovarian syndrome using sequential explanatory mixed method research design. Multidimensional Self-Concept Scale (MSCS) and individual interviews were incorporated in gathering the data. Results clearly proved that the physical and affective self-concept scores significantly differed before and after the facilitation of the MBSR as an intervention. This study confirmed that MBSR enhances the adolescents with PCOS' physical and affective self-concept. Themes that were generated before and after MBSR facilitation were analyzed using the thematic analysis which further established finding to address the dearth of studies about this topic and as a basis for the efficacy of MBSR.